Karakterisasi Dinamis Tegangan Primer dan Sekunder pada Transformator Auxiliary akibat Beban Motor yang Berubah - Ubaidah; Fahrur Riza Priyana; Yudi Eka Putra; Sony Ferbangkara (Department of Electrical Engineering, Faculty of Engineering, Universitas Lampung, 2025)
Auxiliary transformers play a crucial role in maintaining the stability of electrical systems, especially when facing load changes caused by motor disconnection. This study aims to analyze the impact of current and voltage on Unit 3 auxiliary transformer due to the disconnection of vacuum pump motor A (500 kW) and vacuum pump motor B (500 kW) from the system. Simulations were conducted under three main conditions: normal operation without load disconnection, disconnection of vacuum pump motor A, and simultaneous disconnection of both vacuum pump motors A and B. The simulation results indicate that under normal conditions without load, the current and voltage on the primary side of the transformer are 283.9 A and 11 kV, while on the secondary side they are 495.7 A and 6.212 kV. When vacuum pump motor A is disconnected, transient current and voltage on the primary side range from 257.8 A to 250.1 A, with voltage fluctuating from 11 kV to 11.033 kV. In the case of both motors being disconnected, transient current and voltage on the primary side range from 231.8 A to 217.3 A, with voltage changing from 11 kV to 11.067 kV, while on the secondary side, the current drops from 404.7 A to 379.4 A, and voltage increases from 6.212 kV to 6.304 kV. These findings provide a clear depiction of the dynamic characteristics of the auxiliary transformer due to motor load variation and its impact on the stability of the electrical system.